A study to investigate the functional rehabilitation outcomes of patients undergoing physical rehabilitation at Gugulethu Community Health Centre - Pegram, Elizabeth Anne (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.